Pengaruh Nilai Perusahaan, Konservatisme Terhadap Opini Audit Going Concern dan Kualitas Laba - Surjadi, Merna; Sofianty, Dianmonalisa; Whittleliang Hakki, Tandry; Pohan, Pricilla (Dinasti Research, 2024)
Every entity has an obligation to provide financial reports to stakeholders. Auditors have an important role as intermediaries between stakeholders as users of financial reports and entities or companies as providers of financial reports. Going concern is the ability of a business unit to maintain its survival for a reasonable period of time, which is no more than one year from the date of the audited financial statements This study aims to test two influences, namely the influence of Company Value and conservatism on the going concern audit opinion carried out by the company and the influence of Company Value and conservatism on Earnings Quality. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the period 2019-2021. The type of data used in this study is secondary data in the form of financial reports of companies that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Firm Value has an effect on Earnings Quality, but Conservatism have not effect on Earnings Quality. Based on the results of this study, it shows that Firm Value has an effect on Opinion Audit Going Concern, but Conservatism have not effect on Opinion Audit Going Concern